OPTIMIZING INPATIENT SATISFACTION: EXAMINING THE IMPACT OF SERVICE QUALITY AT LAMADDUKKELLENG SENGKANG HOSPITAL IN WAJO DISTRICT - Fachry, Zul; Rachmat, Zul (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This study aims to identify and analyze the influence of service quality on the level of patient satisfaction at Lamaddukkelleng Sengkang Hospital in Wajo District. The hospital, as a public service institution, faces a primary challenge related to the discrepancy between service delivery and patient expectations. In an effort to maintain trust and patient satisfaction, Lamaddukkelleng Sengkang Hospital is required to enhance the quality of its services. The research employs a quantitative approach, collecting primary data through questionnaires distributed to 89 inpatients. Statistical analysis using SPSS 26.0 indicates that service quality significantly influences the level of patient satisfaction. The correlation between service quality and patient satisfaction variables, at 0.368, suggests a positive yet weak influence. The analysis also reveals that overall, service quality is categorized as fairly good, with some indicators needing improvement to achieve an excellent level. Meanwhile, the overall level of patient satisfaction is considered good, but there is still room for improvement. The findings of this research provide a comprehensive overview of the relationship between service quality and patient satisfaction at Lamaddukkelleng Sengkang Hospital, laying the groundwork for the development of improvement strategies and enhanced services in the future